Bio-Oss® blocks combined with BMP-2 and VEGF for the regeneration of bony defects and vertical augmentation - Schmitt, Christian; Lutz, Rainer; Döring, Hendrik; Lell, Michael; Ratky, Jozsef; Schlegel, Karl Andreas (Clinical Oral Implants Research, 2013)
Objectives: The aim of this study was to evaluate the bone formation rate and osseointegration of Bio-Oss® blocks combined with rhBMP-2 and rhVEGF in bony defects and after vertical augmentation. Material and methods: Bio-Oss® blocks plus rhBMP-2 (BMP), Bio-Oss® blocks plus rhVEGF (VEGF), or Bio-Oss® blocks plus rhBMP-2 and rhVEGF (BMPVEGF) were inserted in "critical size defects" (CSD) in the calvariae of adult pigs. Control defects were filled with collagen carrier (Lyostypt®) plus growth factors and untreated Bio-Oss® blocks (CO). In a second group, Bio-Oss® blocks plus growth factors and untreated Bio-Oss® blocks were used for vertical augmentation of the calvariae. In the first group, the investigation time was 30 days, in the second group it was 30 and 60 days. The bone samples were investigated histomorphometrically, and the newly formed bone (BV/TV) was judged by microradiographic investigation. Results: In the CSD model, the newly formed bone in the region of interest was not significantly different within the groups. In the second setting, the inserted bone blocks exhibited sufficient volume stability with increasing bone formation up to 9.33% ± 3.92% for BMP, 10.42% ± 1.81% for BMP/VEGF, 11.01% ± 4.78% for VEGF, and 10.02% ± 5.43% for the control group after 60 days. Conclusion: In the chosen setting and time frame, de novo bone formation did not increase with the additional use of growth factors.
CRIS-Team Scopus Importer:2024-05-13
Keywords: Animal experiments; Biomaterials; Bone implant interactions; Bone regeneration; Bone substitutes; Growth factors; Guided tissue regeneration